ZHENG May Contribute to Obesity Phenotypes Based on Body Composition: A Pilot Study on the Traditional Chinese Medicine Approach. (10th March 2014) - Tao, Feng; Lu, Hao; Oppert, Jean-Michel; Basdevant, Arnaud
Abstract : Objective. Obesity therapy needs new approaches to complement current phenotyping systems. This study aims to assess associations between the Traditional Chinese Medicine (TCM) ZHENG and obesity phenotypes. Methods . We assessed medical history and habitual physical activity and measured body composition, fasting plasma glucose and insulin, and lipids. We collected TCM data through face-to-face interview. ZHENG elements (essentials and locations) were identified by TCM practitioner. Primary ZHENG was assessed by cluster analysis. Results. In 140 consecutive subjects enrolled in a university clinic (body mass index (BMI): 39.9 ± 5.8 kg/m2), ZHENG essentials were identified as "QiXu, " "Re, " "YinXu, " and "TanShi" (totally 86.8%). Locations were "Shen, " "Wei, " "Pi, " and "Gan" (totally 91.8%). Four types of primary ZHENG were identified: A (37.1% of subjects), B (16.5%), C (35.7%), and D (10.7%). Subjects in type D showed elevated BMI, total fat mass (FM), FM index, trunk FM, and less physical activity, as compared with others. Subjects in type B changed regional body composition (reduced trunk FM% and elevated appendicular FM%). Biological parameters did not differ across primary ZHENG clusters. Conclusions . Obesity phenotypes based on body composition differ according to ZHENG in obese patients. This study is a first step toward understanding the contribution of TCM to obesity phenotyping.